2006
DOI: 10.1007/s10915-006-9090-z
|View full text |Cite
|
Sign up to set email alerts
|

One-sided Post-processing for the Discontinuous Galerkin Method Using ENO Type Stencil Choosing and the Local Edge Detection Method

Abstract: ], a one-sided post-processing technique for the discontinuous Galerkin method was introduced for reconstructing solutions near computational boundaries and discontinuities in the boundaries, as well as for changes in mesh size. This technique requires prior knowledge of the discontinuity location in order to determine whether to use centered, partially one-sided, or one-sided post-processing. We now present two alternative stencil choosing schemes to automate the choice of post-processing stencil. The first i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The SIAC filtering increases the inter-element continuity up to C k−1 and raises the convergence rate of the DG solution from order k + 1 to order 2k+1 (i.e., superconvergence) for linear [9] and nonlinear [15,18,17] hyperbolic equations solved over a uniform mesh, and variable coefficient euqations [17,24]. The proof has also been extended for local derivative computation [29] and boundary filtering [30,4,13]. Convergence properties of SIAC filtering and its effectiveness have been widely studied in the literature [9,19,6,12,14,16].…”
Section: Siac Filter Reviewmentioning
confidence: 94%
“…The SIAC filtering increases the inter-element continuity up to C k−1 and raises the convergence rate of the DG solution from order k + 1 to order 2k+1 (i.e., superconvergence) for linear [9] and nonlinear [15,18,17] hyperbolic equations solved over a uniform mesh, and variable coefficient euqations [17,24]. The proof has also been extended for local derivative computation [29] and boundary filtering [30,4,13]. Convergence properties of SIAC filtering and its effectiveness have been widely studied in the literature [9,19,6,12,14,16].…”
Section: Siac Filter Reviewmentioning
confidence: 94%
“…[8,10,33]. Other application areas include the determination of the interface which separates two or more different material media [12,30] and the enhancement of some numerical algorithms [2].…”
Section: The Edge Detection Problemmentioning
confidence: 99%
“…We need some previous definitions e, = (x! -25) 2 Figure 4 shows the interface (F J ) of / 2 . The results obtained are reported in Table 5.…”
Section: General Piecewise Constant Function With Tubular Tree-like Imentioning
confidence: 99%
“…It has been shown in [10,18,20] that spectral accuracy can be recovered in smooth regions for nonlinear conservation laws using the spectral viscosity method. It has also been recently demonstrated that high order accuracy in smooth regions can be recovered with suitable post-processing of the WENO method [11], and of the discontinuous Galerkin method [1]. Hence we are motivated to develop a method that determines not only the discontinuities in piecewise smooth functions, but the discontinuities in each successive derivative function as well.…”
Section: Introductionmentioning
confidence: 99%